MUTU GURU DALAM PROSES PEMBELAJARAN MELALUI PENERAPAN SUPERVISI KLINIS DI SDN 006/XI AUR DURI - Emi Suswita (Program Studi PGSD FKIP Universitas Bung Hatta, 2019)
The purpose of this study was to determine the application of the clinical supervision of school principals in SDN 006 / XI Aur Duri, Pondok Tinggi District to improve the quality of teachers in the learning process of 2018/2019 Academic Year. The background of this research is still the low quality of education is far from what is expected, especially in SDN 006 / XI Aur Duri District Pondok Tinggi Kota Sungai Penuh. To overcome this problem, researchers as well as school principals provide guidance to teachers through clinical supervision, and this action as an appropriate step so that improving teacher quality achievement can be achieved in accordance with government programs, namely quality education programs. Subjects in this study were SDN 006 / XI Aur Duri Teachers in Pondok Tinggi District which was the place for researchers to work. The action is carried out in 3 cycles. Activities carried out in the even semester of the 2018/2019 school year. The duration of research for 6 weeks is effectively carried out from 10 September to 26 October 2018. In implementing the action, the design is carried out in 3 cycles which include; (1) planning, (2) action, (3) observation, (4) reflection. In collecting data the technique used is observation and questionnaire. Based on the results of the research above, improving the quality of teachers in the learning process, through the development of clinical supervision is very good results. This was evident at the first meeting of the 11 teachers who were present at the time of the study the average grade reached; 67.73% increased to 71.27% and in cycle 3 increased to 75.91%. Based on Ministerial Regulation No 12 of 2007 on the competencies of teachers and principals, and can make work plans for school work, and can organize schools towards the desired changes reaching 85% of their achievements, then clinical supervision is said to be effective. Thus the hypothesis proposed above can be accepted.